Flexihaus house design for disaster victim - Hanafi, Zulkifli (2008)
Disaster in the hot humid climate region can be catasthrophic. The after effect of disaster is not limted to the lost of lives but properties including homes. The condition may be worsen by inadequate and late relief respond. One of the most critical issue in disaster striken areas are the provision of adequate and suitable transit accommodation. The fastest an suitable system of shelter accommodation available is by using the prefabrication based on local materials. In the current research a system known as ‘FLEXIHAUS’ which has the advantage of speed and simplicity in construction is the most recent innovation in disaster houses in the hot and humid climate of Malaysia.